2009
DOI: 10.1071/he09048
|View full text |Cite
|
Sign up to set email alerts
|

Computer-tailored weight reduction interventions targeting adults: a narrative systematic review

Abstract: The evidence of effectiveness for computer-tailored primary prevention interventions for weight reduction is limited to a small number of heterogeneous studies. There is uncertainty whether reported effects are generalisable and sustained. The relative success of different components of efficacious interventions and the optimal intervention intensity and tailoring methods are unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…25,56 reported similar outcomes in that they did not influence weight but affected health behaviors such as fruit and vegetable intake, which may influence longterm weight maintenance. [56][57][58][59] The majority of participants in Project YEAH (68%) were at a normal weight, similar to the recent American College Health Association National College Health Assessment 60 population in which 62% reported normal weight. Although participants in this study tended to be of normal weight, National Health and Nutrition Examination Survey 2009-2010 1,2 reported that 67% of males and 56% of females in the 20-to 39-year age range had a BMI $ 25 kg/m 2 .…”
Section: Discussionsupporting
confidence: 67%
“…25,56 reported similar outcomes in that they did not influence weight but affected health behaviors such as fruit and vegetable intake, which may influence longterm weight maintenance. [56][57][58][59] The majority of participants in Project YEAH (68%) were at a normal weight, similar to the recent American College Health Association National College Health Assessment 60 population in which 62% reported normal weight. Although participants in this study tended to be of normal weight, National Health and Nutrition Examination Survey 2009-2010 1,2 reported that 67% of males and 56% of females in the 20-to 39-year age range had a BMI $ 25 kg/m 2 .…”
Section: Discussionsupporting
confidence: 67%
“…eHealth interventions were superior to control or comparison strategies in 21 of 41 studies (51 percent), 24 studies had indeterminate results, and in four studies comparison groups outperformed eHealth intervention groups. In a systematic review of RCTs for computertailored weight loss strategies, half of the 6 interventions showed significant positive results [41]. Vandelanotte et al [42] reviewed RCT and quasi-experimental studies of website-delivered physical activity interventions and found that 8 of 15 studies showed improvements in physical activity, but positive results diminished after 6 months.…”
Section: Evidence From Ehealth Research On Interventions?mentioning
confidence: 98%
“…H. Marcus et al, 2007;Neville, Milat, & O'Hara, 2009;Neville et al, 2009aNeville et al, , 2009b, smoking cessation, and other risk behaviors (Revere & Dunbar, 2001;Rimer & Glassman, 1998;Strecher, 1999;Strecher, Wang, Derry, Wildenhaus, & Johnson, 2002).…”
mentioning
confidence: 95%